A statistical approach to quantify the impact on voltage quality caused by PV generators - Saadat, N.; Choi, San Shing; Vilathgamuwa, D. (2011)
A probabilistic method is proposed to evaluate voltage quality of grid-connected photovoltaic (PV) power systems. The random behavior of solar irradiation is described in statistical terms and the resulting voltage fluctuation probability distribution is then derived. Reactive power capabilities of the PV generators are then analyzed and their operation under constant power factor mode is examined. By utilizing the reactive power capability of the PV-generators to the full, it is shown that network voltage quality can be greatly enhanced. © 2011 IEEE.